Adipose‐derived mesenchymal stem cells therapy for acute kidney injury induced by ischemia‐reperfusion in a rat model. (12th October 2017) - Zhang, Jian‐Bo; Wang, Xiao‐Qiao; Lu, Guo‐Lin; Huang, Huan‐Sen; Xu, Shi‐Yuan
Summary: Acute kidney injury (AKI) represents a group of complicated syndromes with a high mortality rate. The administration of adipose‐derived mesenchymal stem cells (ADMSCs) has been tested as a possible treatment method for AKI. The long‐term evaluation of AKI induced by ischemia/reperfusion (IR) and the probable renal protection of ADMSCs are limited. In this study we have established a rat AKI model induced by IR and investigated the possible protective effects of ADMSCs. Adult Sprague‐Dawley (SD) rats were divided into three groups (n = 6/each group). The MOCK group was as the normal control. Rats in the IR‐AKI and IR‐AKI+ADMSCs groups were subjected to IR injury by clamping both renal pedicles for 40 minutes. Rats in the MOCK and IR‐AKI groups were injected with PBS via the tail vein as negative treatment controls. Rats in the IR‐AKI+ADMSCs group received ADMSCs therapy (2 × 10 6 cells were injected into the rats via the tail vein). We found that ADMSC transplantation restored the pathologic morphology induced by IR‐AKI to normal compared with the MOCK group, suggesting the reparative function of ADMSCs in kidney tissues. Compared with IR‐induced AKI alone, ADMSC treatment significantly decreased the number of apoptotic cells, the level of total urinary protein and serum creatinine, the expression of pro‐inflammatory cytokines (IL‐6, TNF‐α, IL‐1β, IFN‐γ, TNF‐α, IFN‐γ, and TGF‐β), and the inflammation‐associated proteins (HGF and SDF1), but increased the expression of the anti‐inflammatory cytokine, IL‐10, and the anti‐apoptotic regulator, Bcl‐2. Our data have indicated that ADMSC transplantation may protect against IR‐induced AKI by anti‐apoptotic and anti‐inflammatory effects.